Effect of Low-volume Exchange Transfusion on Neonatal Hyperbilirubinaemia: A Retrospective Cohort Study - Manu Rajan Idicula; Krishna Kumar Diwakar; Leela Sudhakaran Kamath (JCDR Research and Publications Pvt. Ltd., 2024)
Introduction: A double volume exchange transfusion for hyperbilirubinaemia often requires more than one pack of compatible blood to fulfil the calculated volume. This is often unavailable, necessitating exchange transfusion using less than the calculated double-volume. During practice, the authors found that many patients had a positive therapeutic response even when the exchange blood volume was reduced. Aim: To study the effect of the reduced volume of blood used for exchange transfusion in neonates with hyperbilirubinaemia. Materials and Methods: A retrospective cohort study was conducted in the Neonatal Intensive Care Unit (NICU), Malankara Orthodox Syrian Church Medical College (tertiary level), Kerala, India, between January 2015 and December 2020. Total 116 patients who underwent exchange transfusion for hyperbilirubinaemia, regardless of gestational age, were included. Pre- and postexchange details, blood chemistry and haemogram were collected from the records and analysed. The patients were grouped into group 1 (80-≤120 mL/kg) and group 2 (>120-≤160 mL/kg) based on the volume of blood used for exchange transfusion. The correlation of exchange blood volume with the percentage drop in bilirubin, rebound rise of bilirubin at six hours, duration of phototherapy, and duration of admission was studied using Pearson's/Spearman's correlation. Data were statistically analysed using Independent samples t-test, Paired sample t-test, and Chi-square test to determine, if there was a significant difference between the groups. Results: Out of 116 patients, group 1 had 67 (57.78%) patients, and group 2 had 49 (42.24%) patients. The mean±Standard Deviation (SD) gestational age was 37.6±1.57 weeks, and 59 (50.86%) were males. The mean±SD postexchange bilirubin was 13.12±3.85 mg/dL in group 1 and 10.26±2.78 mg/dL in group 2, resulting in a bilirubin reduction of 40.74±12.81% and 53.81±11.67%, respectively. The rebound bilirubin at six hours (13.15±4.32 mg/dL vs 11.23±2.30 mg/dL) made no clinical difference in the management of the patient. The median duration of phototherapy was 48 hours, and the median duration of admission was five days in both groups. Conclusion: Exchange transfusion with a lower volume of blood, followed by phototherapy, can lead to a clinically acceptable reduction in serum bilirubin. Non availability of the exact 160 mL/kg of blood for exchange is not an adequate reason to delay exchange transfusion.